Pelatihan Pembuatan Video Audio Visual Sebagai Inovasi Pembelajaran, Media Ekspresi dan Penunjang Siswa pada Mata Pelajaran Seni Budaya Di SMP Negeri 1 Jatirogo - Stri Agneyastra Dite (Abdi Seni, 2023)
Practically, the subject of Culture and Arts at schools is closely related to the advancement of information technology. However, the utilization remains low, causing the instructional process to be less innovative. Knowledge of art and culture in the subject should be an expressive, interactive, and dynamic lesson if technology is used as one of the teaching-learning media. One example is the creation of audiovisual videos about art and culture. A training was created for selected junior high school students at SMP Negeri 1 Jatirogo to make audiovisual short films. The purpose is to teach knowledge on using one of the latest advancements in information technology, particularly audiovisual video, and a participative learning experience that differs from past techniques. The approach employed is participatory, with students serving as learning resources to improve soft skills and abilities in processing and applying concepts in audiovisual form and training to be autonomous and responsible in the learning process. The outcomes of this program provide new ideas for instructors, particularly Cultural and Arts teachers, to create further learning innovations for more engaging, expressive, and apprehensible class meetings through audiovisuals. Another outcome is that students gain diverse learning experiences, including an understanding of short filmmaking, which is another approach to incorporating arts into learning, particularly in Culture and Arts.